Experimental investigation of the two-photon widths of the chi(c0) and the chi(c2) mesons. - Eisenstein, B; Ernst, J; Gladding, G; Gollin, G; Hans, R; Johnson, E; Karliner, I; Marsh, M; Plager, C; Sedlack, C; Selen, M; Thaler, J; et al. (2001)
Using 12.7 fb(-1) of data collected with the CLEO detector at CESR, we observed two-photon production of the cc states chi(c0) and chi(c2) in their decay to pi(+)pi(-)pi(+)pi(-). We measured gamma(gammagamma)(chi(c))xB(chi(c)-->pi(+)pi(-)pi(+)pi(-)) to be 75+/-13(stat)+/-8(syst) eV for the chi(c0) and 6.4+/-1.8(stat)+/-0.8(syst) eV for the chi(c2), implying gamma(gammagamma)(chi(c0)) = 3.76+/-0.65(stat)+/-0.41(syst)+/-1.69(br) keV and gamma(gammagamma)(chi(c2)) = 0.53+/-0.15(stat)+/-0.06(syst)+/-0.22(br) keV. Also, cancellation of dominant experimental and theoretical uncertainties permits a precise comparison of gamma(gammagamma)(chi(c0))/gamma(gammagamma)(chi(c2)), evaluated to be 7.4+/-2.4(stat)+/-0.5(syst)+/-0.9(br), with QCD-based predictions.